2022
DOI: 10.1186/s12864-022-08706-2
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of okra (Abelmoschus esculentus): using nanopore long reads to investigate gene transfer from chloroplast genomes and rearrangements of mitochondrial DNA molecules

Abstract: Background Okra (Abelmoschus esculentus L. Moench) is an economically important crop and is known for its slimy juice, which has significant scientific research value. The A. esculentus chloroplast genome has been reported; however, the sequence of its mitochondrial genome is still lacking. Results We sequenced the plastid and mitochondrial genomes of okra based on Illumina short reads and Nanopore long reads and conducted a comparative study betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…The polymorphisms in the conformation of the plant mitochondrial genome always puzzle us. Our results also supported the representation that plant mitogenomes should be considered a dynamic genome, at least, this structure is a more complete description of complicated plant mitogenomes ( Li et al., 2022 ). The most complicated structure was observed in the B. papyrifera mitogenome because it has six repeats that could mediate 19 kinds of connections, but the B. monoica mitogenome had two repeats controlling seven kinds of connections.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The polymorphisms in the conformation of the plant mitochondrial genome always puzzle us. Our results also supported the representation that plant mitogenomes should be considered a dynamic genome, at least, this structure is a more complete description of complicated plant mitogenomes ( Li et al., 2022 ). The most complicated structure was observed in the B. papyrifera mitogenome because it has six repeats that could mediate 19 kinds of connections, but the B. monoica mitogenome had two repeats controlling seven kinds of connections.…”
Section: Discussionsupporting
confidence: 84%
“…During the evolutionary history, massive original mitochondrial genes have transferred into nuclear region for more stable inner environment or functional efficiency across different lineages ( Wicke et al., 2011 ) and about 30 to 50 encoding genes remained. The three Broussonetia mitogenomes shared 36 unique genes including 23 PCGs, two rRNA genes, and 11 tRNA genes, and several tRNA genes were lost in B. kaempferi and/or B. papyrifera ( Table 1 , Figure 2 ), which was common in other species such as Dalbergia odorifera ( Hong et al., 2021 ) and Abelmoschus esculentus ( Li et al., 2022 ). The conservation in gene content across many plant lineages indicated the stable function of the mitogenome as it is responsible for the basic energy synthesis for life activities through oxidative phosphorylation ( Mackenzie and McIntosh, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…The melon ( Cucumis melo L.) mitogenome is over 2.7 Mb in size, eight times larger than that of other cucurbits, and contains a large number of repeat sequences and a high content of nucleus-derived DNA, accounting for 42% and 47% of the total sequence ( Rodríguez-Moreno et al., 2011 ), respectively. The high frequency of recombination mediated by three pairs of long repeats in the okra ( Abelmoschus esculentus ) mitogenome results in four molecules existing at the same time ( Li et al., 2022 ). Acer truncatum and Glycine max contain numerous foreign sequences, and most genes with transferred sequences are tRNA genes ( Chang et al., 2013 ; Ma et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mitogenome of plants is more complex in structure than that of other eukaryotes. In addition to a master circular molecule, it also includes linear conformations, branched structures, and numerous small circular molecules mediated by repeat sequences ( Notsu et al., 2002 ; Kozik et al., 2019 ; Li et al., 2022 ). For example, the mitogenome of Populus simonii was assembled into three circular molecules, and all of them had protein-coding capability ( Bi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the size of the repeats is closely related to the frequency of recombination [ 63 ]; namely, the frequency of recombination mediated by short repeats tends to be lower than that mediated by long repeats. For example, in Nymphaea colorata Peter [ 64 ], Scutellaria tsinyunensis C. Y. Wu et S. Chow [ 65 ] and Abelmoschus esculentus (L.) Moench [ 66 ], the long repeats had high recombination frequencies, and the short repeats had lower recombination frequencies; all of the repeats identified in the Prunus salicina Lindl. [ 67 ] mitogenome were short repeats, and they all had low recombination frequency.…”
Section: Discussionmentioning
confidence: 99%